Evaluation and Improvement of the Stability of Poly(ethylene oxide)‐based Solid‐state Batteries with High‐Voltage Cathodes. Issue 12 (10th February 2023) - Yusim, Yuriy; Trevisanello, Enrico; Ruess, Raffael; Richter, Felix H.; Mayer, Alexander; Bresser, Dominic; Passerini, Stefano; Janek, Jürgen; Henss, Anja
Abstract: Solid‐state batteries (SSBs) with high‐voltage cathode active materials (CAMs) such as LiNi1− x − y Co x Mn y O2 (NCM) and poly(ethylene oxide) (PEO) suffer from "noisy voltage" related cell failure. Moreover, reports on their long‐term cycling performance with high‐voltage CAMs are not consistent. In this work, we verified that the penetration of lithium dendrites through the solid polymer electrolyte (SPE) indeed causes such "noisy voltage cell failure". This problem can be overcome by a simple modification of the SPE using higher molecular weight PEO, resulting in an improved cycling stability compared to lower molecular weight PEO. Furthermore, X‐ray photoelectron spectroscopy analysis confirms the formation of oxidative degradation products after cycling with NCM, for what Fourier transform infrared spectroscopy is not suitable as an analytical technique due to its limited surface sensitivity. Overall, our results help to critically evaluate and improve the stability of PEO‐based SSBs. Abstract : The failure of cells in poly(ethylene oxide) (PEO)‐based solid‐state lithium batteries at high voltages, indicated by "voltage noise" and attributed to the formation of lithium dendrites, was effectively overcome by using higher molecular weight PEO. In addition, the PEO/NCM interface was investigated by X‐ray photoelectron spectroscopy confirming oxidative degradation of PEO.